PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN (Perusahaan Perbankan yang terdaftar di BEI tahun 2019 -2022) - Siti Khopipah; Roni Roni; Yenny Ernitawati (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to examine the effect of Corporate Social Responsibility and Company Size on Company Financial Performance. The population in this study was obtained using purposive sampling method with the aim of obtaining a sample that was in accordance with the research variables. The population of this study used mining companies listed on the IDX in the 2019-2022 period. Based on the selection criteria, a sample of 48 companies was obtained. The statistical method used to test the research hypothesis is multiple regression analysis. The results of this study indicate that CSR has a positive effect on the company's financial performance, this means that the increase in social responsibility activities will get support from stakeholders and trust in the community which can increase the company's financial performance. The size of the company has a negative effect on the company's financial performance, which means that the higher the total assets of the company does not always increase the value of the company's financial performance, this can be caused by a lack of strategy and not paying careful attention to the management of bureaucracy and their operational efficiency to reduce their negative impact on financial performance.